Sociological theory in the digital age - Ignatow, Gabe ca. 20./21. Jh (Routledge, 2020)
"What is the role of sociological theory in the information age? What kinds of theories are best suited to analysing the social uses of digital technologies, and for using digital technologies in new ways to study the social? This book contributes to several ongoing conversations on how the social sciences can best adapt to contemporary information technologies and information societies. Focusing on practical or 'usable theory, ' it surveys the challenges and opportunities of conducting social science in the information age, as well as the theoretical solutions that sociologists have developed and applied over the last two decades. With specific attention to three theoretical approaches in digital social research - critical theory, forensic theory and Bourdieusian theory - the author provides an overview of the history and main tenets of each, surveys its use in sociological research, and evaluates its successes and limitations. Taking a long-term view of theoretical development in evaluating schools of thought and considering their productivity in analysing and using contemporary digital communication technologies, this book thus treats theory as a tool for empirical research and the development of theory as inseparable from research practice. As such, it will appeal to scholars of sociology and social theory with interests in research methods, the development of theory and digital technologies"--
Keywords: Social sciences / Research; Information technology; Digitalisierung; Soziologie; Theorie